2021
DOI: 10.1038/s41467-021-23326-2
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyzed cycloaromatization of vinylsilanes with arylsulfonylazides

Abstract: Sila-molecules have recently attracted attention due to their promising applications in medical and industrial fields. Compared with all-carbon parent compounds, the different covalent radius and electronegativity of silicon from carbon generally endow the corresponding sila-analogs with unique biological activity and physicochemical properties. Vinylsilanes feature both silyl-hyperconjugation effect and versatile reactivities, developing vinylsilane-based Smiles rearrangement will therefore provide an efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…However, the existing methods mainly focus on forming furanyl Csp 2 –SO 2 bond in the C2/C3-position of benzofurans, the fabrication of the Csp 3 –SO 2 bond into benzofuranyl skeletons is very limited. , Although Lam demonstrated that sulfonyl radicals preferentially attacked the alkynyl moiety instead of the allyl group of allyl-tethered alkynes to enable the coupling–cyclization of enynes (Scheme a), vinylsilanes generally possess richer electron density than allyl CC double bonds due to the weaker electronegativity of the Si element and silyl hyperconjugation effect, leading to radicals that possibly prefer to attack the vinyl group instead of the alkynyl moiety. Therefore, we recently developed an Ir­(III)-catalyzed cycloaromatization of ortho -alkynylaryl vinylsilanes with arylsulfonyl azides for assembling naphthyl-fused benzosiloles under photoredox conditions, in which arylsulfonyl azides were employed as aryl radical precursors to be trapped by vinylsilanes via α-silyl radical Smiles rearrangement (Scheme b) . Our mechanism studies confirmed that the Si/O switch significantly affected the reactivity of vinylethers possibly due to the p−π conjugated effect between the oxygen’s lone pair and the CC double bond, leading to the formation of Csp 3 –SO 2 bonds.…”
Section: Introductionmentioning
confidence: 60%
“…However, the existing methods mainly focus on forming furanyl Csp 2 –SO 2 bond in the C2/C3-position of benzofurans, the fabrication of the Csp 3 –SO 2 bond into benzofuranyl skeletons is very limited. , Although Lam demonstrated that sulfonyl radicals preferentially attacked the alkynyl moiety instead of the allyl group of allyl-tethered alkynes to enable the coupling–cyclization of enynes (Scheme a), vinylsilanes generally possess richer electron density than allyl CC double bonds due to the weaker electronegativity of the Si element and silyl hyperconjugation effect, leading to radicals that possibly prefer to attack the vinyl group instead of the alkynyl moiety. Therefore, we recently developed an Ir­(III)-catalyzed cycloaromatization of ortho -alkynylaryl vinylsilanes with arylsulfonyl azides for assembling naphthyl-fused benzosiloles under photoredox conditions, in which arylsulfonyl azides were employed as aryl radical precursors to be trapped by vinylsilanes via α-silyl radical Smiles rearrangement (Scheme b) . Our mechanism studies confirmed that the Si/O switch significantly affected the reactivity of vinylethers possibly due to the p−π conjugated effect between the oxygen’s lone pair and the CC double bond, leading to the formation of Csp 3 –SO 2 bonds.…”
Section: Introductionmentioning
confidence: 60%
“…The reaction scope was capable of varying substituents on each phenyl ring involved in the cascade and producing unusual, bridged structures upon changing the vinylsilane to an allylsilane group. 54 Scheme 16 Radical Smiles cascade producing silicon-based heterocyclic scaffolds (W. Zeng and co-workers)…”
Section: Short Review Synthesismentioning
confidence: 99%
“…The reaction scope was capable of varying substituents on each phenyl ring involved in the cascade and producing unusual, bridged structures upon changing the vinylsilane to an allylsilane group. 54…”
Section: Radical Smiles: Alkene and Alkyne Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Li employed 4CzIPN/Cu­(OTf) 2 as a combinated catalysis system to achieve a visible-light-catalyzed decarboxylative radical sulfonylation of sulfinates with redox-active aliphatic carboxylic esters (Scheme b) . More recently, we still described a photocatalyzed coupling–cyclization of sulfonylazides with vinylethers and vinylsilanes to furnish complex oxa- and sila-cycles via denitrogenation, respectively . Based on the fact that diazo esters, sulfonylazides, and sulfonylhydrazones possess similar multinitrogen skeletons, we therefore envisioned that sulfonylhydrazones could also possibly undergo photocatalytical denitrogenation to directly afford arylsulfones under mild conditions (Scheme c).…”
mentioning
confidence: 99%